EFEKTIVITAS MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS 1 SDN SAWAH BESAR 1 - Charirotud Dini Aulia; Choirul Huda; Mira Azizah (STKIP Subang, 2024)
This research was motivated by the low learning outcomes of students in the learning outcomes of Indonesian language learning due to students not learning regularly, lack of innovation during direct learning activities and not using less attractive learning models. So that students are less enthusiastic and less active in learning activities. This research focuses on the cognitive aspects of students by using the Problem Based Learning learning model on the learning outcomes of grade 1 students of SDN Sawah Besar 1 Semarang City. This study used an experimental quantitative research method with a pre-experimental type of one group pretest posttest using data collection in the form of tests containing 30 multiple[1]choice questions given to students. This research was conducted in grade 1 of SDN Sawah Besar 1 with a total of 31 students, 15 men, 16 women. This research was conducted for 3 findings. There is an improvement in learning outcomes, in using the inquiry learning model. Data analysis techniques use SPSS version 25 which includes validity and reliability tests, prerequisite tests, and hypothesis tests. The results showed that at the time of the preetest the lowest score was 20, the highest was 70, students completed KKM 7, did not complete KKM 24, and an average of 46.19. While the lowest posttest results of posttest students are 30 and those who do not meet the KKM are 5 students. The highest score was 96 and those who met the KKM score amounted to 26 students with an average of 79.38. The results of the hypothesis test of t test results on learning outcomes in the table above showed a sig value of 0.004<0.05 then Ho was rejected and Ha was accepted. This is also supported by the results of t count> t table which is 3.498> 2.042. With that, it can be said that the Problem Based Learning learning model is effective for the learning outcomes of grade 1 students of SDN Sawah Besar 1 Semarang City.